Abuse liability for esketamine in a cohort of patients undergoing an acute treatment course to manage treatment-resistant depression: a secondary analysis of an observational study in real-world clinical practicee - Gilmar Gutierrez; Gustavo Vazquez; Nisha Ravindran; Raymond W. Lam; Peter Giacobbe; Karthikeyan Ganapathy; Annette Kowara; André Do; Anusha Baskaran; Sean Michael Nestor; Jennifer Swainson (Therapeutic Advances in Drug Safety)
Background: Intranasal (IN) esketamine has become an effective and well-tolerated therapeutic option for the management of treatment-resistant depression within major depressive disorder (MDD-TRD). Despite these promising benefits, given the prevalence of ketamine abuse, concerns remain over the addiction liability that may be associated with esketamine treatment. Objectives: The objective of this study is to assess the real-world abuse liability of this substance by tracking changes in likeability and cravings through an acute treatment course. Design: This is a secondary analysis of a previously published multicenter observational study. Methods: Likeability and craving for esketamine were assessed using the Likeability and Cravings Questionnaire (LCQ) in MDD-TRD patients receiving an acute course of IN esketamine treatment (eight dosing sessions). The data were analyzed using descriptive statistics, multivariate analysis of variance (MANOVA), and pre-post effect size (Cohen’s d ). Results: Twenty-three patients (52.2% female, 43.5 ± 11.9 years old) were assessed. Most patients reported a neutral liking and no cravings for esketamine after their first dosing session. These metrics did not increase significantly by treatment endpoint. MANOVA showed that neither age, sex, baseline depression scores, the presence of side effects, or the study site had a statistically significant impact on LCQ scores either alone or in combination. Conclusion: These results agree with the available literature, showing that an acute course of IN esketamine treatment was not associated with high levels of drug liking or cravings, and this did not increase through the course of eight treatments. Though larger studies are needed, esketamine does not appear to be associated with significant abuse liability when used in an acute course of treatment for patients with MDD-TRD. These are important results for this patient population and for clinical practice.